The Algorithmic Path to Wellness: How AI is Revolutionizing Sustainable Lifestyle Changes - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The pursuit of a healthier life is a universal aspiration, yet maintaining sustainable lifestyle changes remains a persistent challenge for many. In the rapi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning